2010
DOI: 10.1002/mana.200910086
|View full text |Cite
|
Sign up to set email alerts
|

Elliptic operators with general Wentzell boundary conditions, analytic semigroups and the angle concavity theorem

Abstract: We prove a very general form of the Angle Concavity Theorem, which says that if ((T(t)) defines a one parameter semigroup acting over various L^p spaces (over a fixed measure space), which is analytic in a sector of opening angle \theta_p, then the maximal choice for \theta_p is aconcave function of 1-1/p. This and related results are applied to get improved estimates on the optimal L^p angle of ellipticity for a parabolic equation of the form {\partial u}{\partial t}=Au, where A is a uniformly elliptic second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…In the same papers [11,12], under C ∞ regularity assumptions on ∂Ω, on all the coecients of A and on β, γ, we also showed that the closure of the realization of A in X p , 1 < p < ∞, is m-dissipative and generates an analytic semigroup having sector of analyticity depending on the moduli of ellipticity of A. Moreover, its domain can be explicitly described.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…In the same papers [11,12], under C ∞ regularity assumptions on ∂Ω, on all the coecients of A and on β, γ, we also showed that the closure of the realization of A in X p , 1 < p < ∞, is m-dissipative and generates an analytic semigroup having sector of analyticity depending on the moduli of ellipticity of A. Moreover, its domain can be explicitly described.…”
mentioning
confidence: 64%
“…Existence and analyticity results for the semigroup associated with A remain true also for more general elliptic versions of A, equipped with the corresponding (GW BC). See [11]. It is very important to point out that there is a precise physical derivation of (GWBC), as it was shown in details by G.R.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This is an extremely tough problem in general. For some related complementary results, see [6]. Chapter 6 deals with partial differential operators of order higher than two.…”
Section: Theorem 2 (Hille-yosida Generation Theorem) An Operator a Imentioning
confidence: 99%
“…We have become aware that Favini et al [5] have recently obtained the result stated in Theorem 1.2 with a different approach.…”
Section: Proof Of Theorem 12mentioning
confidence: 99%